Rational cybersecurity for business : the security leaders’ guide to business alignment (2020)
This book is a Security Leaders’ Guide to aligning with the business. If you are a Chief Information Security Officer (CISO), Head of Security with a similar title, a security manager, or a security team member providing leadership to the business, this book is for you.